All-inorganic halide perovskite CsPbBr3@CNTs composite enabling superior lithium storage performance with pseudocapacitive contribution. (20th January 2021) - Liu, Shuai; Zhang, Ke; Tan, Lu; Qi, Shaopeng; Liu, Guoning; Chen, Jinxi; Lou, Yongbing
Highlights: The specific composite composed of carbon nanotubes (CNTs) tightly wrapped perovskite-CsPbBr3 (CsPbBr3 @CNTs) was synthesized by a simplified co-precipitation method. The CsPbBr3 @CNTs was applied as anode in lithium ion batteries for the first time. The CsPbBr3 @CNTs composite showed excellent lithium storage capacity supplied with surface dominating pseudocapacitive contribution. Abstract: All-inorganic halide perovskites have recently made remarkable achievements in the field of photo-electrochemistry, but rarely been applied in energy storage devices, especially, in lithium-ion batteries (LIBs). In this article, the specific composite composed of carbon nanotubes (CNTs) tightly wrapped perovskite-CsPbBr3 (CsPbBr3 @CNTs) was synthesized by a simplified co-precipitation method. Attributed to the specific morphology, the CsPbBr3 @CNTs composite supplied short pathways for the transport of both electrons and lithium ions, along with the interface for pseudocapacitive behavior. The synergistic effects of CsPbBr3 and CNTs enhanced the pseudocapacitive effect, thus, CsPbBr3 @CNTs exhibited high cycling stability and rate capability. The prominent lithium storage capabilities were exhibited then, with first reversible capacity of 644.6 mA h g −1 /100 mA g −1 and maintained at 470.2 mA h g −1 after 200 cycles. Moreover, under the large current density of 600 mA g −1, it kept a stable capacity of 203.8 mA h g −1 . This study, for the very first time, proved the great application potential of all-inorganic perovskite composite materials with surface dominating pseudocapacitive contribution in LIBs. Graphical abstract: Image, graphical abstract